Predictors of psychological stress in silica‐exposed workers in the artificial stone benchtop industry. Issue 6 (14th April 2022) - Hore‐Lacy, Fiona; Hansen, Jessy; Dimitriadis, Christina; Hoy, Ryan; Fisher, Jane; Glass, Deborah; Sim, Malcolm R.
Abstract: Background and objective: Artificial stone benchtops are a popular kitchen product, but dust from their preparation and installation contains respirable crystalline silica, which causes silicosis. Silicosis is a preventable, permanent lung disease. The aim of this study was to assess mental health in workers from the artificial stone benchtop industry at risk of silicosis. Methods: Workers from the artificial stone benchtop industry undergoing assessment for silica‐associated disease were included. Information on demographics; occupational, medical and smoking history; modified Medical Research Council dyspnoea scale; Perceived Stress Scale (PSS‐10) questionnaire; spirometry; and chest x‐ray was collected. Univariate and multivariate regression analyses were conducted. Results: Of the 547 participants, the majority were men, aged under 45 years, in the industry for less than 10 years. With each increase of dyspnoea score, PSS‐10 scores increased. Higher PSS‐10 scores were also observed in those no longer in the industry, with a history of anxiety or depression, attending assessment early in the programme and a medium exposure duration. Participants who used an interpreter reported lower stress. No difference was observed across job title, age, sex, smoking, spirometry or chest x‐ray categories after multivariate analysis. Conclusion: This study identified workers with dyspnoea as likely to report higher stress. Other factors, such as leaving the industry, early attendance and a history of anxiety or depression, are also helpful in identifying workers at risk of poorer mental health outcomes. Abstract : This study describes psychological stress scores in silica‐exposed workers from the artificial stone benchtop industry and identifies predictors of elevated stress. See related Editorial